Сто великих сражений Второй мировой - Лубченков Юрий Николаевич (Сто великих, 2011)
Экземпляры: СБ (201506) / Инвентарный номер: 51254 / Цена: 206.03 / Сис.шифр: 63.3(2)62 / Авт.знак: Л82 / ГРНТИ: 03 / ББК: 63.3(2)62